Methods of the companions in receiving the prophetic hadith after the death of Prophet Muhammad - Akila, Mamat; Shumsuddin, Yabi; Aminuddin, Ahmad@Basir; Fadlan, Mohd Othman (2019)
After the death of the Prophet (peace and blessings of Allah be upon him), the Companions realized that the revelation had stopped. The Companions reacted by finding ways which can help them preserve the Prophetic Hadith. The expansion of the Islamic territories and the abundance of incidents and events had made the narration of the Prophetic Hadith a necessity. The Companions have made tremendous efforts in the service of the Prophetic Hadith in order to it to the next generation. This library research is aimed to record these efforts and to derive the methods of the Companions in receiving the Prophetic Hadith from the Prophet –Peace be upon him- after his death. This study also explain the diversity and the importance of those methods. These methods included first, emphasizing on asking one another even though if performing a journey is necessary. Second, verification and vigilance in the narration. Third, their command to reduce the narration of the Prophetic Hadith in fear of error or forgetfulness. Fourth, oath adjuration to the narrator and repetition of hearing in heterogeneous time. These efforts have resulted in preserving the Prophetic Hadith from elimination and fraud.